Neonatal Hyperoxia Exposure Disrupts Axon–Oligodendrocyte Integrity in the Subcortical White Matter - Ritter, Jonathan (Society for Neuroscience, 2013)
The pathological mechanisms underlying neurological deficits observed in individuals born prematurely are not completely understood. A common form of injury in the preterm population is periventricular white matter injury (PWMI), a pathology associated with impaired brain development. To mitigate or eliminate PWMI, there is an urgent need to understand the pathological mechanism(s) involved on a neurobiological, structural, and functional level. Recent clinical data suggest that a percentage of premature infants experience relative hyperoxia. Using a hyperoxic model of premature brain injury, we have previously demonstrated that neonatal hyperoxia exposure in the mouse disrupts development of the white matter (WM) by delaying the maturation of the oligodendroglial lineage. In the present study, we address the question of how hyperoxia-induced alterations in WM development affect overall WM integrity and axonal function. We show that neonatal hyperoxia causes ultrastructural changes, including: myelination abnormalities (i.e., reduced myelin thickness and abnormal extramyelin loops) and axonopathy (i.e., altered neurofilament phosphorylation, paranodal defects, and changes in node of Ranvier number and structure). This disruption of axon–oligodendrocyte integrity results in the lasting impairment of conduction properties in the adult WM. Understanding the pathology of premature PWMI injury will allow for the development of interventional strategies to preserve WM integrity and function.